SISTEM INFORMASI PENCARIAN LOKASI PERGURUAN TINGGI DI MAKASSAR - Irwan Irwan; Dedy Atmajaya (ILKOM Jurnal Ilmiah, 2018)
Universities are generally spread in various locations even though in one province (district or city). This study specializes in universities in the city of Makassar. The college location has information related to spatial and non-spatial data, such as name, address and information related to the college. The problem faced in this study is that not everyone knows about universities in the city of Makassar, especially the location of the college. The method used in this study is the Haversine Formula and Euclidean method. Results of the study using the Haversine Formula method, the measurement of the distance of the closest trajectory to college are smaller or closer than using the Euclidean method. Because the Haversine Formula method ignores the height of hills and depths of valleys on the earth's surface.Â  The purpose of this study is to facilitate in informing the general public who need information from universities in Makassar.